Stress as a helpful psychophysiological state under conditions of competitive activity of young underwater swimmers - Lyashenko, A. (New Collegium, 2021)
In the article the research of stress state and its impact on the effectiveness of competitive activities of teen-age swimmers of underwater is given. Starting conditions for development of state stress in young swimmers of underwater, its influence on the effectiveness of competitive activity and availability of a great number of teen-age swimmers of underwater with weak nervous system are determined. But the level of stress depends not only from teen-ages nervous system. It is result is using psychology methods long time during and how them couches force take part in the competitions. All of it for training them nervous system to strong stress. To mind somebody of physiologys, really stress reaction may be will not manifest future. First of recommendation is special psychological training. Arming young athletes with means of regulation them maind with an early age. Second of recommendation every trainer is must be able to designate aim and motivate young athletes to start. And last, level the tension of the nervous system of adolescents is not defined by us as negative factor performances in competitions of the underwater sport.